2017
DOI: 10.3989/mc.2017.05116
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance assessment of half warm recycled asphalt mixes containing up to 100 % RAP

Abstract: ABSTRACT:The use of Half Warm Mixes with high Reclaimed Asphalt content (HWMRA) has the potential to generate significant environmental advantages such as the reduction in consumption of natural resources and the emission of gases into the atmosphere. This paper therefore focuses on demonstrating the viability of using these types of mixes in wearing courses. For this purpose, an HWMRA with 70 % and 100 % Reclaimed Asphalt Pavement (RAP) and emulsion were designed in the laboratory. The performance of the mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The chamber has different response types depending on the kind of test being performed; where the temperature control system used has a damped sub behavior with a steady-state error for the temperature of about ± 2.5 ° C and humidity to ± 2.5% RH, this is due in principle to the control operation, the ability to respond of the caloventor to the reference and the thermal properties and hydrophobic material [13], [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chamber has different response types depending on the kind of test being performed; where the temperature control system used has a damped sub behavior with a steady-state error for the temperature of about ± 2.5 ° C and humidity to ± 2.5% RH, this is due in principle to the control operation, the ability to respond of the caloventor to the reference and the thermal properties and hydrophobic material [13], [14].…”
Section: Resultsmentioning
confidence: 99%
“…When the chamber is operating exclusively with humidity control, it is obtained a transient response over-damped and steady-state error of about ± 5% RH, because the humidification system is slow to respond since the structure has properties optimum sealing with the hydrophobic properties of the material, allow to maintain stable conditions in the chamber with minimum loss [14], [15].…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the recycled mixture displayed higher mechanical resistance as a result of the partial blending of the fresh bitumen with the RAP containing aged bitumen. Lizárraga et al [14,15] analyzed the performance of HWMAs containing 70% and 100% RAP in the laboratory and in situ. They used a prototype plant for the manufacture.…”
Section: Mixturementioning
confidence: 99%
“…Therefore, many of the studies found in the literature review have focused on the heating and healing of mixtures containing only virgin (i.e., aggregates or fresh bitumen) and steel slag aggregates. In this sense, it has been suggested that HWRA technologies with recycled and slag aggregates are promising solutions to increase further environmental, technical, and economic benefits associated with the use of industrial by-products [64,65]. In this regard, González et al [42] concluded that mixtures with RAP and metal fibers have the potential to increase the self-healing effect on the cracked specimens when using microwave heating energy.…”
Section: Introductionmentioning
confidence: 99%